2016
DOI: 10.1158/1078-0432.ccr-16-0338
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Early Phase Trials Sponsored by the National Cancer Institute: An Analysis of Corrective Action Plans to Improve Accrual

Abstract: Accruing patients in a timely manner represents a significant challenge to early phase cancer clinical trials. The NCI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Similarly, even for nonaccelerated programs, the inclusion of robust pharmacokinetics can be helpful to inform the need for further dose refinement (26). Although the inclusion of pharmacokinetics sampling was not mentioned specially as a reason for slow study accrual in the review by Massett and colleagues (31), to reduce both patient and operational burden, appropriate sampling schedules, which coincide with scheduled patient visits, should be encouraged, as the knowledge gathered from such evaluations can be essential to guide and refine dosing and inform future drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, even for nonaccelerated programs, the inclusion of robust pharmacokinetics can be helpful to inform the need for further dose refinement (26). Although the inclusion of pharmacokinetics sampling was not mentioned specially as a reason for slow study accrual in the review by Massett and colleagues (31), to reduce both patient and operational burden, appropriate sampling schedules, which coincide with scheduled patient visits, should be encouraged, as the knowledge gathered from such evaluations can be essential to guide and refine dosing and inform future drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Such oral drugs held additional appeal for patients with mCRPC, whose only available option at that time was intravenous chemotherapy. Notably, as reported by Massett et al [9], the National Cancer Institute recognized competing trials as a reason for slow accrual in phase II studies. They proposed to invest in earlier accrual planning as a better strategy for future trials.…”
Section: Investigator's Assessmentmentioning
confidence: 91%
“…In this issue of Clinical Cancer Research, Massett and colleagues (1) describe the many challenges facing accrual to early-phase clinical trials sponsored by the NCI (Bethesda, MD), analyze proposed ways to increase accrual, and assess the utility of corrective action plans (CAP) to improve accrual.…”
mentioning
confidence: 99%
“…The letter includes an accrual summary and a request for a CAP, providing explanation for slow accrual and proposing means of improvement to achieve enrollment goals. Massett and colleagues (1) reported that CAP requests were made for 46% of CTEP IND-holding studies active from August 2011 through February 2013, indicating that a significant number of trials did not accrue as planned. Safety and toxicity were primary concerns cited for slow accrual to phase I trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation